2016
DOI: 10.1039/c6cp03533g
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into the photochemistry of avobenzone in gas phase and acetonitrile from ab initio calculations

Abstract: Avobenzone (4-tert-butyl-4'-methoxydibenzoylmethane, AB) is one of the most widely used filters in sunscreens for skin photoprotection in the UVA band. The photochemistry of AB includes keto-enol tautomerization, cis-trans isomerization, rotation about the single bond and α bond cleavages of carbonyl groups. In this contribution we study chelated and non-chelated enol, rotamers Z and E, and keto tautomers of AB in the ground and excited states in gas phase and acetonitrile by means of a coupled cluster method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…This disagreement mirrors the previous reported issues in predicting relative energies values for the neutral keto and enol tautomers of dibenzoylmethane systems without anharmonic methods. 27,69 Many of these previous papers also identified twisted Z and E rotamer geometries. Our conformational search identified many such twisted forms, but their relative energies lay at much higher energies (> 40 kJ/mol and 30 kJ/mol using the ωB97XD and M06-2X functionals, respectively) so they have been omitted from this work.…”
Section: Quantum Chemical Calculations Of Gas-phase and Solution-phase Ab•hmentioning
confidence: 98%
See 1 more Smart Citation
“…This disagreement mirrors the previous reported issues in predicting relative energies values for the neutral keto and enol tautomers of dibenzoylmethane systems without anharmonic methods. 27,69 Many of these previous papers also identified twisted Z and E rotamer geometries. Our conformational search identified many such twisted forms, but their relative energies lay at much higher energies (> 40 kJ/mol and 30 kJ/mol using the ωB97XD and M06-2X functionals, respectively) so they have been omitted from this work.…”
Section: Quantum Chemical Calculations Of Gas-phase and Solution-phase Ab•hmentioning
confidence: 98%
“…1,[23][24] AB is a dibenzoylmethane derivative and a member of a family of molecules known to take multiple isomerization pathways following UV excitation. [25][26][27][28][29][30] Photoexcitation of AB is believed to lead to nonadiabatic population of high-lying S0 vibrational levels, which can lead to isomerization to a less photostable form. 31 Previous photolysis experiments performed in hexane have shown that this photodegradation of AB occurs by a Norrish type 1 mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Computational work on neutral AB by Kojićet al showed that under both gaseous and solvated conditions (MeCN), the S 1 state of CE has a T 1 state of alternate spin parity available energetically within the zero-point-energy window of S 1 at the Franck−Condon geometry. 27 If T 1 is accessed, there is a flat potential about the out-of-plane OH dihedral coordinate which crosses the contorted S 0 state. An easily accessible T 1 state for Ea/Eb at S 1 Franck−Condon geometries may facilitate the rearrangements shown in Scheme 4.…”
Section: Irmpd Spectroscopy Of Ab•h +mentioning
confidence: 99%
“…[10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The perplexity caused by the relative stability of the asymmetric and symmetric DBM's protic tautomers is due to the inability of experimental scattering and spectroscopic techniques to resolve ultrafast proton motion in the hydrogen bond, but also possibly due to various experimental conditions and aggregate states in which DBM was studied. [10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] The perplexity caused by the relative stability of the asymmetric and symmetric DBM's protic tautomers is due to the inability of experimental scattering and spectroscopic techniques to resolve ultrafast proton motion in the hydrogen bond, but also possibly due to various experimental conditions and aggregate states in which DBM was studied.…”
Section: The Effects Of Hydrogen Bonding and Homogeneous Electric Fiementioning
confidence: 99%